2021
DOI: 10.3390/cancers13184499
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols: Promising Adjuvants for Colorectal Cancer Therapies

Abstract: Colorectal cancer (CRC) is a major cancer type and a leading cause of death worldwide. Despite advances in therapeutic management, the current medical treatments are not sufficient to control metastatic disease. Treatment-related adverse effects and drug resistance strongly contribute to therapy failure and tumor recurrence. Combination therapy, involving cytotoxic treatments and non-toxic natural compounds, is arousing great interest as a promising more effective and safer alternative. Polyphenols, a heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Dietary adjuvant therapy is a personalized treatment method in which functional foods are added to the patient’s basic diet to achieve the purpose of treatment according to the patient’s individual condition. Dietary adjuvant therapy has been widely used in adjuvant therapy along with surgery, radiotherapy, and chemotherapy. , There are no side effects of dietary adjuvant therapy, and cheap food materials will not economically burden the patients . Furthermore, dietary adjuvant therapy does not produce a strong sense of pain, such as that of surgery and radiotherapy, which is of considerable benefit to cancer patients who have been suffering from illness for a long time .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary adjuvant therapy is a personalized treatment method in which functional foods are added to the patient’s basic diet to achieve the purpose of treatment according to the patient’s individual condition. Dietary adjuvant therapy has been widely used in adjuvant therapy along with surgery, radiotherapy, and chemotherapy. , There are no side effects of dietary adjuvant therapy, and cheap food materials will not economically burden the patients . Furthermore, dietary adjuvant therapy does not produce a strong sense of pain, such as that of surgery and radiotherapy, which is of considerable benefit to cancer patients who have been suffering from illness for a long time .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new strategies are needed to develop novel therapeutic options and increase the efficacy of current treatments. Many authors suggest combination therapies using conventional chemotherapeutic agents with dietary supplements, as well as phytotherapeutic agents [ 53 , 54 , 55 ]. In this work, we showed that PMEO synergizes with cisplatin in an in vitro synergism study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pharmacological studies have demonstrated that polyphenolic compounds exhibit strong antioxidant effects and display obvious antitumor potential [ 11 , 12 , 13 ] ( Figure 1 ). In the combat against tumors, much attention has been paid to the development of polyphenolic compounds sourced from natural products because of their low toxicities and abundance of resources [ 14 , 15 ]. However, polyphenolic compounds derived from natural products also have some drawbacks, such as low stability, weak targeting ability, and poor solubility and bioavailability, which limit their applications in the clinical treatment of cancers [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%